Cervical artery dissection goes frequently undiagnosed - Grond-Ginsbach, Caspar; Metso, Tiina M.; Metso, Antti J.; Pezzini, Alessandro; Tatlisumak, Turgut; Hakimi, Maani; Grau, Armin J.; Kloss, Manja; Lichy, Christoph (Medical hypotheses, 2013)
Cervical artery dissection (CeAD) is a frequent cause of stroke among young patients. It is unclear how many CeADs occur asymptomatically or cause subtle and unspecific clinical symptoms. We hypothesize that CeAD remains often unrecognized. Accordingly, the incidence of CeAD might be higher and the stroke risk lower than generally assumed. Lack of CeAD-indicating clinical symptoms is regarded as the main cause of missed diagnoses. We further hypothesize that underrepresentation of asymptomatic and oligosymptomatic patients in CeAD studies may have biased the association between ischemia and local symptoms in CeAD patients as well as the associations of CeAD with risk factors or co-morbidities. We finally hypothesize that symptomatic CeAD may be preceded by an initial asymptomatic phase. According to this final hypothesis, the time of onset of CeAD should be considered uncertain. The issue of unrecognized CeAD is relevant, as it may affect the associations between CeAD and putative risk factors. Furthermore, the existence of clinically silent CeADs may explain why recurrent and familial CeAD have been rarely observed.
Gesehen am 11.03.2021